The power of partnerships: Academic and high school libraries collaborate for student research success. Issue 2 (10th June 2019) - Groves, Christy
Abstract : Purpose: A large, predominantly undergraduate university in Tennessee partnered with a local magnet school aiming to assist high school seniors with their college-level research assignment. The partnership began as a pilot, but quickly expanded to include other high schools as a result of initial successes. This paper aims to describe the development of the partnership and its importance in fulfilling a key component of college preparedness for gifted high school students. Design/methodology/approach: This paper describes how the Library partnership commenced as a service to a local high school that required its students to access college-level research materials. The paper details how both the Library and the high school recognized the impact of collaborating to expose these students to the information literacy skills needed for college readiness. Findings: The paper presents the challenges encountered when attempting to provide college-level information literacy instruction to large groups of students visiting a college campus. It concludes with best practices and lessons learned, as well as plans for formal assessment and future initiatives. Originality/value: The author has presented at Library Instruction West, July 2018. A review of the professional literature demonstrates that other academic libraries have partnered with local schools for a variety of library-related initiatives. Therefore, the concept of partnerships between the Library and local high schools is not unique. However, this paper aims to describe challenges encountered, best practices, lessons learned and suggestions for future directions, including formal assessment, all of which could be adapted by other academic libraries as applicable.